2007
DOI: 10.3892/ijmm.19.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of poly(adenosine diphosphate-ribose) polymerase by the active form of vitamin D

Abstract: Abstract. Vitamin D is well characterized for its role in mineral homeostasis and maintenance of normal skeletal architecture. Vitamin D has been demonstrated to exert antiinflammatory effects in a variety of disease states including diabetes, arthritis and inflammatory bowel disease. In these diseases poly[adenosine diphosphate (ADP)-ribose] polymerase (PARP) inhibitors have also proved effective as anti-inflammatory agents. Here we present data demonstrating that the active metabolite of vitamin D, 1α,25-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…PARP1 activity has previously been shown to be regulated by various endogenous factors (including xanthines, purines, estrogen) (Virag and Szabo, 2001;Mabley et al, 2005;Geraets et al, 2006;Szabo et al, 2006;Mabley et al, 2007) and has been shown or suggested to be regulated/phosphorylated by protein kinase C, mitogen-activated protein kinase, and extracellular signal-regulated kinases 1 and 2 (Tanaka et al, 1987;Kauppinen et al, 2006;Hegedus et al, 2008). Based on the current findings, we conclude that the cAMP/PKA system represents an additional mode of the regulation of its activity via phosphorylation.…”
Section: Discussionsupporting
confidence: 70%
“…PARP1 activity has previously been shown to be regulated by various endogenous factors (including xanthines, purines, estrogen) (Virag and Szabo, 2001;Mabley et al, 2005;Geraets et al, 2006;Szabo et al, 2006;Mabley et al, 2007) and has been shown or suggested to be regulated/phosphorylated by protein kinase C, mitogen-activated protein kinase, and extracellular signal-regulated kinases 1 and 2 (Tanaka et al, 1987;Kauppinen et al, 2006;Hegedus et al, 2008). Based on the current findings, we conclude that the cAMP/PKA system represents an additional mode of the regulation of its activity via phosphorylation.…”
Section: Discussionsupporting
confidence: 70%
“…SIRT1 is downstream in ROS signaling, but can be importantly upstream in regulating cellular levels such as activation of FOXO3 (164), muscle ringfinger protein 1 (MuRF1) (8), and protein kinase B (Akt) (382). Therefore, these NAD-dependent metabolic sensors are regulating redox signaling in a wide array (222).…”
Section: Exercise and Redox Signalingmentioning
confidence: 99%
“…It is a stress protein, which can, however, promote neuronal death. In fact, there is an overexpression of PARP1 in the substantia nigra of PD patients [281]; increased levels of vitamin D down regulate PARP-1 expression, probably mediated by a diminishment of microglial activation [282]. All these aspects considered, clinical trials on vitamin D supplementation in Parkinson's disease have been carried out [283].…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%